Influence of operating factors on accurate digging depth control of the remote-controlled explosive disposal machine / Dat Duy Nguyen, Dat Van Chu and Sy Le Van - Nguyen, Dat Duy; Chu, Dat Van; Van, Sy Le (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
In this study, a dynamic model of the operating equipment and the hydraulic drive system of the remote-controlled explosive disposal machine were built to ensure both kinetic accuracy of digging path and the effective cutting angle. The Ruppel's control approach was applied to study the dynamics of the whole system and the influence of the arm-controlled signal, the soil digging resistance on the digging control process. In addition, a simulation model of the entire system is also performed to deeply understand the dynamic behaviour.